Implementation of Multi-service IEEE 802.11e Block Acknowledgement Policies - Cabral, Orlando Manuel Brito (2009)
Optimisation of IEEE 802.11e MAC protocol performance can be performed by modifying several parameters left open in the standard, like buffer size and acknowledgement policies. In this work, an event driven simulator was developed, and a comparison of the results between the case of standalone services and several services supported simultaneously was addressed. With only a single service, higher values for the goodput are obtained for video and background (BK) traffics, while the lowest ones are found for the voice application. Besides, the number of supported users is higher for voice. With mixtures of traffic, when the number of station is small the goodput is lower for voice. However, for higher number of station, the lowest values of the goodput occur for background traffic. By using the Block Acknowledgement procedure, for video and background traffics in a single service situation, the capacity was improved in the case when the number of stations is equal or higher than 16 and 12, respectively. However, for lower values of the number of stations, the use of Block Acknowledgements leads to a slightly worst system performance. In a scenario with mixture of services the most advised block size is 12 (less delay in a highly loaded scenario). The total number of supported user increases from 30 to 35.